Late effect of larval co-exposure to the insecticide clothianidin and fungicide pyraclostrobin in Africanized Apis mellifera - Tadei, Rafaela; Domingues, Caio E. C. [UNESP]; Malaquias, José Bruno; Camilo, Erasnilson Vieira; Malaspina, Osmar [UNESP]; Silva-Zacarin, Elaine C. M. (Springer Nature, 2019)
Among the factors that contribute to the reduction of honeybee populations are the pesticides. These chemical compounds reach the hive through forager bees, and once there, they can be ingested by the larvae. We evaluated the effects of repeated larval exposure to neonicotinoid insecticide, both in isolation and in combination with strobilurin fungicide, at environmentally relevant doses. The total consumption of the contaminated diet was 23.63 ng fungicide/larvae (pyraclostrobin) and 0.2364 ng insecticide/larvae (clothianidin). The effects on post-embryonic development were evaluated over time. Additionally, we assessed the survival pattern of worker bees after emergence, and the pesticides’ effects on the behavior of newly emerged workers and young workers. Young bees that were exposed to the fungicide and those subjected to co-exposure to both pesticides during larval phase showed behavioral changes. The insecticide, both in isolation and in combination with fungicide reduced the bees’ longevity; this effect of larval exposure to pesticides was stronger in bees that were exposed only to the insecticide. Although the larvae did not have sensitivity to exposure to pesticides, they showed later effects after emergence, which may compromise the dynamics of the colony, contributing to the reduction of the populations of bees in agroecosystems.